Impact of high‐altitude therapy on type‐2 immune responses in asthma patients. Issue 1 (3rd November 2019) - Boonpiyathad, Tadech; Capova, Gertruda; Duchna, Hans‐Werner; Croxford, Andrew L.; Farine, Herve; Dreher, Anita; Clozel, Martine; Schreiber, Juliane; Kubena, Petr; Lunjani, Nonhlanhla; Mirer, David; Rückert, Beate; et al.
Abstract: Background: Asthma patients present with distinct immunological profiles, with a predominance of type 2 endotype. The aim of this study was to investigate the impact of high‐altitude treatment on the clinical and immunological response in asthma. Methods: Twenty‐six hospitalized asthma patients (nine eosinophilic allergic; EA, nine noneosinophilic allergic; NEA and eight noneosinophilic nonallergic; NN) and nine healthy controls in high altitude for 21 days were enrolled in the study. We assessed eosinophils, T cells, Tregs, and innate lymphoid cells (ILC) from peripheral blood using flow cytometry. Results: The number of eosinophils (both resting and activated) and chemoattractant receptor homolog expressed on Th2 cells (CRTH2)‐expressing CD4 + and CD8 + T cells decreased significantly in EA patients after altitude treatment. The frequency of CRTH2 + Tregs as decreased significantly in all the asthma phenotypes as well as the frequency of ILC2 was significantly reduced in EA after altitude treatment. After 21 days of altitude therapy, CRTH2‐expressing ILC2, CD4 + and CD8 + T cells and Treg cells showed attenuated responses to exogenous PGD2. Furthermore, PGD2 signaling via CRTH2 was found to diminish the suppressive function of CRTH2 + Tregs which partially normalized during high‐altitude treatment. Improved asthma control was particularly evident in allergic asthma patients and correlated with decreased frequencies of CRTH2 + Treg cells in EA patients. Serum IL‐5 and IL‐13 decreased during climate treatment in asthma patients with high baseline levels. Conclusions: Asthma treatment in high altitude reduced the type 2 immune response, corrected the increased CRTH2 expression and its dysregulated functions. Abstract : High‐altitude therapy of asthma reduces the frequencies of chemoattractant receptor homolog expressed on Th2 cells (CRTH2) innate lymphoid cells, activated eosinophils, helper and cytotoxic T cells. CRTH2 + T regulatory cells are defective in their suppressive function and show less suppressive function in PGD2‐stimulated cultures. High‐altitude therapy improves asthma symptoms associated with the correction of dysregulated type‐2 and T regulatory responses. Abbreviations: CRTH2, Chemoattractant receptor‐homologous molecule expressed on TH2 cells; PGD2, Prostaglandin D2